Oncology Drug Development and Approval of Systemic Anticancer Therapy by the U.S. Food and Drug Administration. (20th December 2012) - Martell, Robert E.; Sermer, David; Getz, Kenneth; Kaitin, Kenneth I.
Abstract : Background: Regulatory approval of oncology drugs is the cornerstone of the development process and approval characteristics shape eventual utilization. Approval trends and characteristics provide valuable information for drug developers and regulators and ultimately affect clinicians and patients. Methods: Indication characteristics were tabulated for drugs approved by the U.S. Food and Drug Administration (FDA) for systemic therapy of malignancies from 1949 through October 2011. Variables included time to approval, initial/supplemental indication, tumor type, stage of disease, specification of protein expression or genetic information, drug class, trial design, concomitant agent, trial size, and endpoint. Results: A total of 121 unique anticancer agents, including 242 unique indications, were approved. The number of trials for each indication has decreased; however, trial size has increased and more randomized controlled trials have been performed. Trial designs have increasingly used time‐to‐event endpoints and rarely have used symptom‐based primary endpoints. Approvals have been primarily single agent, with less emphasis on palliative treatments and increasing emphasis on advanced disease stages and requirements for prior therapy. Molecular specifications in labels have increased, but they are present in less than 30% of recent indications and are not associated with shorter approval times. Conclusion: Approval of oncology agents is occurring in increasingly more challenging settings, suggesting gaps between eventual practice and development in potentially suboptimal indications. Molecular specifications promise to enhance development, yet widespread use in label indications has not yet been achieved. Abstract : Regulatory approval of oncology drugs is the cornerstone of the development process and approval trends will ultimately affect clinicians and patients. This review examines changes in aspects of drug development over the lifespan of chemotherapy to provide insight into future trends. Abstract : 摘要 背景 . 肿瘤药物获得监管部门批准是研发过程的基础，审批特性决定了最终的用法。审批趋势和特性为药物研发者和监管人员提供了有价值的信息，并最终影响医生和患者。 方法 . 列表介绍从1949年到2011年10月美国食品药品监督管理局（FDA）批准用于恶性肿瘤全身治疗的药物的适应证特性。变量包括批准所需时间、初始/补充适应证、肿瘤类型、疾病分期、蛋白表达或基因信息的属性、药物类别、试验设计、合并药物、试验样本量和终点。 结果 . 共批准121种抗癌药的242项单独的适应证。每项适应证的试验数下降，但试验样本量有所增加，完成的随机对照试验更多。试验设计越来越多使用至事件的时间作为终点，很少采用基于症状的主要终点。审批主要是单一药物，不太重视姑息疗法，越来越重视疾病进展期疾病和要求患者以往接受过治疗。适应证中的分子特性描述增加了，但是仅见于不足30%的近期适应证，分子特性描述与审批时间缩短无相关性。 结论 . 肿瘤药物的批准正处于一个越来越具有挑战性的背景下，提示最终的临床实践与研发次佳适应证之间存在差距。分子特性描述有望促进研发，但尚未广泛用于适应证。